Assessment of reliability of the hydrometer by examination of sediment - Stott, Philip; Monye, Priscilla; Theron, Elizabeth (First Southern African Geotechnical Conference, At Sun City, South Africa, 2016)
A fundamental aspect of the characterization of any soil is the assessment of its particle size distribution. While this is relatively easy for the coarse fraction it remains problematic for soil fines particu-larly for the clay fraction. Hydrometer analysis has been the standard tool for fines assessment for many years but there may be serious shortcomings. Nettleship et al. (1997), Savage (2007), Rodrigues et al. (2011) and many others have pointed to a number of problems facing the hydrometer. Some of the questions have been addressed by laser scattering techniques, but others, including completeness of dispersion and the amount of clay carried down with coarser fractions remain problematic. This investigation assesses some aspects of the reliability of the hydrometer by isolating and testing the sand and silt fractions after settlement. Microscopic examination is used to compare the presence of clay in each fraction with that expected according to hydrometer theory
Published Conference Proceedings